QUO VADIS THE ASEAN ROLE IN NATURAL DISASTER MANAGEMENT IN SOUTHEAST ASIA - Natalia Yeti Puspita (Faculty of Law, Universitas Jenderal Soedirman, 2017)
The threats of natural disasters may happen anytime without recognizing national borders. Southeast Asia is an area which is prone to natural disasters. Every year ASEAN both as an interna-tional organization and its members encounter challenges to natural disaster management which is frequently beyond the country capability. This study is descriptive-analytic normative legal research which focuses on the secondary data as the main data. The finding of this study reveals that country is the main actor in natural disaster management based on primary state responsibility principles. The role of ASEAN is only limited to coordinate and facilitate cooperation among parties in providing humanitarian assistance when the natural disaster occurs. The aid has to get approval from the country which suffers from natural disaster. The role of ASEAN is conducted by AHA Center based on AADMER implemented on 2009.Keywords: ASEAN, Southeast Asia, natural disaster management